(untitled) (European Journal of Pure and Applied Mathematics, 2009)
In this paper, we give a characterization on 1-sequence-covering pi-s-images of locally separable metric spaces by means of point-countable sigma-strong n-network consisting of cosmic spaces (sn-second countable spaces, _0-spaces). As an application, we get a new characterization on 1-sequence-covering, quotient pi-s-images of locally separable metric spaces, which is helpful in solving Y. Tanaka and S. Xia’s question in [21].